(3aQGFO GdeYGfi aj TQM MQR GdCeGfis - (3GHf GLQhe , CHh YHO Gddg eMeO Hf eMeO Hf OGhO GdUfgGLj,J (B723 (3g` s
(3ChdgG (B:s
(3HGH hba MeRg hgTGe Ydi GdgeR hMeRI YfO Gdhba Sgd geRg EPG cGf hSW Ch JWQa efRdG s
(3BNQgG (B:s
(3hEfeG PcQgG djMQR efgG hPdc Cfg bGd ai Chd GdHGH jgOjfi hde jbjOg aNGa Cf jONd Ydjg gPG s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B33 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B215s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdbQGAGJ hGdJLhjOs